The Effect of Home Care Service Innovations in Increasing Patient Loyalty and Satisfaction - Yohana Rangga Bela; Joko Sutrisno; Aprin Rusmawati (Open Access Health Scientific Journal, 2020)
Background: The increase in health care costs, large budget cuts make home care services a tool to reduce costs and length of care. As a result, home care services have developed into a complex issue and must be addressed with great care if one of the goals is to provide the best possible outcome for each individual. The purpose of this study was to find out "Study of Home Care Service Innovation in Improving Patient Loyalty and Satisfaction in the City of Kediri". Method: The design of this research is observational analytic with a cross-sectional approach. The sample size is 79 respondents. Sampling research using random sampling, data collection using questionnaires and the calculation process using the Wilcoxon test using SPSS 18.0 error 0.05. Results: The results of this study indicate that most of the respondents (72.2%) with good home care innovation are 57 respondents, most of the respondents (87.3%) with good loyalty are 69 respondents. more than half of respondents (59.5%) With very satisfied patient satisfaction, 47 respondents out of a total of 79 respondents 0.000 which means it is smaller than = 0.05, thus it can be said that H0 is rejected and H1 is accepted. Conclusion: Researchers can conclude that when there are good services carried out by nursing staff or home care services, good results will also be obtained, including patients who can trust and will continue to be loyal in using home care services at Gambiran Hospital, Kediri City